O TACÓGRAFO COMO INSTRUMENTO POSSIVELMENTE CAPAZ DE CONTROLAR A JORNADA DOS MOTORISTAS DE CAMINHÃO EMPREGADOS, NO RAMO DO TRANSPORTE DE CARGAS - Scheliga, Daniel (2012)
The researched theme is the possibility of the truck drivers‟ workday control as employees, who work in the field of cargo transportation, using a device named tachograph, which is a device that registers the vehicle‟s data in which it was installed, also required in all trucks destined to this field. The methodology was a bibliographic review and a documental research. The bibliographic review grounded the aspects related to the workday and the importance of its limitation. Also, it showed the historic class struggle by better work conditions, as well as, the struggle between the studied classes in this work. The documental research, by means of Law Projects and Jurisprudences, aimed to conceptualize the category to be studied, as well as, to analyze the expectations in terms of regulation of the profession and what the courts have decided about the issue.The research was conducted in the following way: Fist, the category it was studied was delimited, performing a wider study about the development of the work in the history, highlighting the classes‟ fight that has always existed in our society. It was tried to demonstrate that this fight is also happening in the classes involved in this work. Second, a report about the development of the highway transportation in Brazil and the past and current governmental policies destined to the development of such a transportation model chosen by the country was made. Also, the workday performed by the employed truck drivers and the fight of the class for better work conditions was highlighted. Finally, a study about the tachograph and which are the information mandatorily registered by it was performed, followed by a jurisprudential research in order to reveal if the courts recognize the usage of such device as a way able to control the truck drivers‟ workday using the information registered by it.